Pengaruh Pemberian Insentif Pajak Bagi Wajib Pajak Terdampak Pandemi Covid-19, Pengetahuan Perpajakan, Dan Tax Awareness Terhadap Kepatuhan Pelaporan Wajib Pajak UMKM Di Kecamatan Tebet Tahun 2020 - Ilham Wahyudi Hasibuana; Tri Djoko Hardjono (Jurnal Ilmu Administrasi Publik, 2021)
The taxpayers’ compliance to improve national state revenues, including the SMEs sector, remain very low. Despite a continued increase in tax revenues every  year,  the  facts  on  the  ground  show  that  the  state’s income from tax is not optimal. The research aims to determine the impact of the tax incentive, tax knowledge, and tax awareness of COVID-19 Pandemic-affected Taxpayers on SMEs taxpayers’ reporting compliance. The research uses the quantitative descriptive method. A questionnaire was used to collect the research data, and the result was then analyzed and calculated to determine the impact of each variable using a double regression method. The result of the research shows that (1) tax incentive is helpful for the compliance of SME taxpayers’ tax reporting in Tebet Sub-District; (2) good tax knowledge would help the community to meet its tax obligations; (3) tax awareness affects the tax reporting compliance of SMEs taxpayers in Tebet Sub-District; (4) tax knowledge and tax awareness simultaneously affect the tax reporting compliance SMEs taxpayers in Tebet Sub-District.